An Automatic Adaptive Edge-based Smoothed Point Interpolation Method for Coupled Flow-Deformation Analysis of Saturated Porous Media. (May 2022) - Salehi Dezfooli, Mojtaba; Khoshghalb, Arman; Shafee, Ashkan
Abstract: An adaptive analysis based on an advanced computational method, referred to as edge-based smoothed point interpolation method (ESPIM), is proposed for numerical analysis of coupled problems in geomechanics. For the adaptive procedure, a simple error indicator derived based on the maximum difference of the strain energy among the three nodes of each background cell is adopted along with a simple automatic h -type local refinement strategy and automatic mesh generator based on the Delaunay triangulation. Novel activation and termination criteria are proposed for initiating and ending adaptivity analysis in each time step. The performance of the proposed adaptive procedure is investigated through three numerical examples. The results show that with the proposed adaptivity procedure, the adaptive ESPIMs have better computational efficiency compared to non-adaptive methods or the general uniform mesh refinement strategy. In particular, it is shown that the proposed termination criteria for the refinement steps ensures that the adaptivity procedure stops when the computational cost of the refinement overweights the resulting gain in the solution accuracy (determined by the user), hence unnecessary refinement steps are avoided in the analysis to yield optimal computational efficiency.